Pengaruh Dosis Dan Lama Pemberian Susu Kedelai Terhadap Kadar Estradiol - Fatma, Inge Devita; .Nasihun, Taufiqurrachman; Isradji, Israhnanto (WELL BEING, 2018)
Soy milk contains isoflavones which are natural estrogens from plants. The content of isoflavones in soy milk influence for endocrine hormone system disruption due to excessive absorption of phytoestrogens, which is feared to affect the development of reproductive organs. This study aims to determine whether the dose and duration of awarding of soy milk affect the level of estradiol. The research design used was experimental with a post test only control group design, which conducted for one month at 24 strains of female mice balb / C, divided into 6 groups namely two control groups and four treatment groups (with 15 and 30 days observation period). The control group was given a non-soybean diet (pellet feed), the treatment group was given soy milk (doses 0.325 and 0.65 mL each mice). Analyzed of data by one way ANOVA test, post-hoc LSD. One Way Anova test earned p value <0.05, this indicates a significant difference in estradiol levels. There is influence of the dosage of awarding of soy milk on the estradiol level of mice.